Estimativa do saldo de radiacao em Jaboticabal (SP) - Andre, R. G B; Volpe, C. A. (My University, 1988)
This work deals with net radiation (Q*) estimates as function of solar radiation (K↓) for the Jaboticabal region in Sao Paulo State. In the same way shows a comparison between measured and Penman estimates net radiations. The data were 207 pairs of net and solar radiation obtained in a net radiometer and a Eppley Piranometer. The results show a good agreement between Q* and K↓ for two periods: spring-summer and autumn-winter. The Penman's equation for Q* underestimates the values for any station with albedo of 0.25. -English summary
Net radiation estimation in Jaboticabal, Brazil
Keywords: net radiation estimation; Penman's equation; solar global radiation; Brazil, Jaboticabal